2017
DOI: 10.1139/apnm-2017-0361
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate and protein intake during exertional heat stress ameliorates intestinal epithelial injury and small intestine permeability

Abstract: Exertional heat stress (EHS) disturbs the integrity of the gastrointestinal tract leading to endotoxaemia and cytokinaemia, which have symptomatic and health implications. This study aimed to determine the effects of carbohydrate and protein intake during EHS on gastrointestinal integrity, symptoms, and systemic responses. Eleven (male, n = 6; female, n = 5) endurance runners completed 2 h of running at 60% maximal oxygen uptake in 35 °C ambient temperature on 3 occasions in randomised order, consuming water (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
172
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(194 citation statements)
references
References 70 publications
(83 reference statements)
17
172
5
Order By: Relevance
“…A previous systematic review has suggested an exercise‐induced hyperthermia threshold of 38.6°C T core for GI barrier integrity loss (DSAT, I‐FABP and endotoxin) to be commonplace (>50% incidence) and of 39.0°C for GI barrier integrity loss to be universal (100% incidence; Pires et al, ). Consistently, previous research supports the notion that MT biomarkers (endotoxin) are less responsive to subtle alterations in GI barrier integrity that were otherwise detected by the DSAT or I‐FABP following exercise (March et al, ; Snipe et al, , ). Positively, no GI barrier integrity or MT biomarker displayed statistical heteroskedasticity in this EHST model, suggestive that absolute reliability was not dependent upon the magnitude of biomarker response.…”
Section: Limitationssupporting
confidence: 78%
See 3 more Smart Citations
“…A previous systematic review has suggested an exercise‐induced hyperthermia threshold of 38.6°C T core for GI barrier integrity loss (DSAT, I‐FABP and endotoxin) to be commonplace (>50% incidence) and of 39.0°C for GI barrier integrity loss to be universal (100% incidence; Pires et al, ). Consistently, previous research supports the notion that MT biomarkers (endotoxin) are less responsive to subtle alterations in GI barrier integrity that were otherwise detected by the DSAT or I‐FABP following exercise (March et al, ; Snipe et al, , ). Positively, no GI barrier integrity or MT biomarker displayed statistical heteroskedasticity in this EHST model, suggestive that absolute reliability was not dependent upon the magnitude of biomarker response.…”
Section: Limitationssupporting
confidence: 78%
“…This response is comparable to numerous similar duration/intensity exercise protocols, such as: 45‐to‐60 min of ~70% watt max normothermic cycling (van Wijck et al, , [61%, Δ 0.306 ng ml −1 ] 2012, [61%; Δ 0.179 ng ml −1 ] and 20–30 min of ~80% VO 2max running (Barberio et al, [46%, Δ 0.297 ng ml −1 ]; March et al, [72%; Δ 0.350 ng ml −1 ]). In comparison, far greater elevations in I‐FABP have been shown following 90–120 min of moderate‐intensity running performed in the heat (30°C; Morrison, Cheung, & Cotter, [663%; Δ 0.203–0.806 ng ml −1 ]; Snipe et al, [288%, Δ 0.897 ng ml −1 ]; 2018 [432%, Δ 1.230 ng ml −1 ]. Given the high sensitivity of I‐FABP to even minor GI injury, it is vital that known extraneous variables (e.g., prandial/hydration status, prior exercise) are tightly controlled prior to investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, carbohydrate presence within the duodenum is a potent nutrient-mediator for hyperaemia in intestinal villi microvasculature (Matherson et al 2000;Rehrer et al 2005). A recent study showed that consumption of 15 g glucose before and every 20 min during running for 2 h at 60% VO 2max in 35ºC ambient temperature resulted in an abolition of exercise associated epithelial injury, compared with water alone (Snipe et al 2016b). Conversely, considering participants that reported the lowest frequency and severity of gastrointestinal symptoms did not have difficulties in tolerating the gut-challenge, but presented substantially elevated plasma I-FABP concentration, the continuation of carbohydrate provisions during the distance test may have attenuated the intestinal epithelial injury without D r a f t 21 promoting further symptoms.…”
Section: Blood Glucose Plasma Cortisol and I-fabp Concentrationmentioning
confidence: 99%